Long-Term Biostability of Pet Vascular Prostheses - Florence Dieval; Foued Khoffi; Riaz Mir; Walid Chaouch; Didier Le Nouen; Nabil Chakfe; Bernard Durand (International Journal of Polymer Science)
PET Vascular prostheses are susceptible to physical modification and chemical degradation leading sometimes to global deterioration and rupture of the product. To understand the mechanisms of degradation, we studied 6 vascular prostheses that were explanted due to medical complications. We characterized their level of degradation by comparing them with a virgin prosthesis and carried out physicochemical and mechanical analyses. Results showed an important reduction of the fabric’s mechanical properties in specific areas. Moreover, PET taken from these areas exhibited structural anomalies and was highly degraded even in virgin prostheses. These results suggest that vascular prostheses have weak areas prior to implantation and that these areas are much more prone to in vivo degradation by human metabolism. Manufacturing process could be responsible for these weaknesses as well as designing of the compound. Therefore, we suggest that a more controlled manufacturing process could lead to a vascular prosthesis with enhanced lifespan.